Número de amostras na análise geoestatística e na krigagem de mapas de atributos do solo - Souza, Zigomar Menezes de; Souza, Gustavo Soares de; Marques Junior, Jose [UNESP]; Pereira, Gener Tadeu [UNESP] (Univ Federal Santa Maria, 2014)
The objective of this study was to analyze different intensities of soil sampling for accuracy in geostatistical analysis and interpolation maps for precision agriculture in the sugarcane area. Soil samples were collected at two regular grids at a depth of 0.00 to 0.20m for granulometric analysis (area 1) and soil fertility (area 2). We compared soil sampling intensities: 208, 105, 58 and 24 points in Area 1 and 206, 102 and 53 points in Area 2. The data were submitted to descriptive analysis and geostatistics. The variograms constructed with 105 points didn't differ from variograms with 208 points, which doesn't occur for 58 and 24 points. The increase of sampling interval and reducing the number of points promote greater error in kriging. Samples with more than 100 points per area did not result in significant improvements in the error of kriging, or differed in the amount of fertilizer applied to the field.
Number of samples in geostatistical analysis and kriging maps of soil properties
Keywords: Spatial variability; variograms; interpolation; Saccharum officinarum